Inovasi Program Hotline “Resleting” dan Pesputakaan Digital “Pepes” untuk Penurunan Laju Stunting di Desa Rancakalong - Mulyawan, Reyhan Januar; Widiowati, Didiet (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
Rancakalong Village is one of the villages in Rancakalong District which based on data from the Sistem Pencegahan Stunting (SIMPATI) still has the largest percentage of stunting children in the sub-district, which is 10.84% with 27 children under five. The Rancakalong Village Government has made several program efforts aimed at reducing stunting rates in Rancakalong Village, ranging from programs from the Village, Programs from the Disctrict and programs from the central government. However, the problem of stunting in Rancakalong Village still cannot be overcome optimally. Low awareness of parents and the public about stunting knowledge, and parenting styles put children at risk of stunting. Through the implementation of assessment in social work community work, the author was able to identify that people in Rancakalong Village need awareness about stunting problems through the implementation of counseling with new digital-based innovations. The result of the study is the novelty of digital-based stunting counseling media through consultation hotline program named Respons Layanan Stunting (RESLETING) and the Perpustakaan Pencegahan Stunting (PEPES) which is a digital library program.